PENGARUH MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT (STM) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA POKOK BAHASAN EKOSISTEM KELAS VII MTs Amilda 3 1 PARADIGMA PALEMBANG - Amilda Amilda; Sulton Nawawi; Uci Minasari (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
The purpose of the study was to determine the effect of the application of learning model ofScience Technology Society (STS) to the ability of understanding the concept of Biologystudents on the subject of VII grade ecosystem MTs Paradigma Palembang. The desain ofstudy used the design of the Nonequivalent Control Group Design with Quasi Experimentalmethod (quasi experiment). These sample included 35 students. Based on the results of theanalysis of students' concept of understanding shows that the implementation of learningusing the model of learning Science Technology Society (STS) is better than theconventional learning model. It can can be seen from the calculation of the t-test showed ofstudents' concept of understanding sig t-value 0.000 < 0,05, then Ha accepted and H0 rejected.The result of analysis of the improvement of the average completeness of the conceptualunderstanding of the experimental class is 48.2% while the students 'understanding of thecontrol class is 29.2%, which means that the students' understanding of the concept of theexperimental class is higher than the understanding of the concept of the control class. This, itcan be concluded that the learning model of Science Technology Society (STS) around effecton understanding the concept of students of class VII MTs Paradigma Palembang